Споредбена анализа на кожни резови направени со хируршки скалпел наспроти електрохируршки кожни резови во пределот на лицевата регија: проспективно рандомизирано клиничко испитување - Пенева, Маргарита (Медицински факултет, УКИМ, Скопје, 2019)
Introduction. Although electrosurgery is gaining popularity lately, it is mainly used for hemostasis and deep layer dissections. The skepticism against its’ use in skin incisions is due to the fear of skin thermal injury with consecutive wound infection, delayed wound healing and bad esthetic result. Materials and methods. One hundred patients who full filled all the inclusive criteria and none of the exclusive criteria were included in this study. In group A comprising 50 patients, cold steel scalpel No 15 was used for the surgical procedure. Electrosurgical microneedle with 0.06mm radius tip and generator unit KLS Martin Electrosurgical Unit ME MB2 set on cutting mode, power 12W was used for performing surgery in group B including the same number of patients. Results. Both the speed of incision (electrosurgery vs. scalpel-3.17 ± 1.3 vs. 2.6 ± 1.1mm/s) and the speed of excision (electrosurgery vs. scalpel-2.1 ± 1.1 vs. 1.69 ± 0.1 mm2/s) were found to be significantly faster in the electrosurgery group. There was significantly less blood loss in the electrosurgery group compared to the scalpel group (mean 0.009 ± 0.006 vs. mean 0.017 ± 0.013 ml/mm2). During the total period of follow up (4 postoperative days) analgesics required 54% of the patients in the scalpel group and 34% of the patients in the electrosurgery group. Even more significant is the fact that patients treated with electrosurgery that needed analgesics had significantly bigger excision area (median 471 vs. median 259 mm/2). Postoperative complications appeared in 22% of the patients operated with scalpel and 18% of the patients operated with electrosurgery. Although statistical analysis did not confirm as significant the difference in complications between the groups, most of the complications were associated with patients operated with scalpel. When scar cosmetic was evaluated, no difference was noted between the groups although during the total period of follow up the POSAS scores in the scalpel group were higher (worst result). At the end of the follow up, both groups had the same patient satisfaction measured by the patients themselves. Conclusion. Electrosurgery presents safe and effective way of work in the facial region. In that matter it is very important to choose the right generator unit’s settings and the right type of electrode.
Докторска дисертација одбранета во 2019 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Владимир Георгиев.
Keywords: surgical scalpel, elecrosurgery, facial regions, scar